Brand management - Grębosz, Magdalena (Wydawnictwo Politechniki Łódzkiej, 2008)
Nowadays, the problems of brand management, strategy, and promotion are an extremely relevant issue. A strong brand constitutes a basic competitive advantage and is one of the factors ensuring the success of a company. Brand management has become an indispensable element of business activity, and the brand itself - an effective marketing tool. Formulating a brand strategy and selecting methods of its promotion depend to a great degree on the type and size of the market on which a company operates. An effective brand must reach consumers and be accepted by them. The creation of a brand with a strong personality is the first step to success. The next step is brand promotion with the use of all communication means such as advertising, public relations, point-of-sale promotion, organization of brand events, sponsoring, or promotion by company personnel. All of these elements allow for establishing and conducting a dialogue with consumers by means of an appropriately prepared process of communication. Successful branding adds customer value and can provide protection from price competition and pressures towards commoditization. The purpose of this book is to introduce you to the theory and practice of branding. This book aims to be concise, returning to and examining the core foundations of branding. The book has necessarily been divided into a number of chapters in order to provide some form of structure. I owe special thanks to prof. dr hab. Tomasz Domanski and dr hab. Jacek Otto, prof. PL, who revised this book.
Keywords: zarządzanie marką; narzędzia marketingowe; strategia marki; aktywność biznesowa; promocja; zarządzanie produktem; brand management; marketing tool; brand strategy; business activity; promotion; product management